Evaluation of Trichorionic versus Dichorionic Triplet Gestations from 2005 to 2016 in a Large, Referral Maternity Center - Peress, Danielle A.; Peaceman, Alan M.; Yee, Lynn M. (American Journal of Perinatology, 2017)
Objective To evaluate trends in the proportions and outcomes of dichorionic–triamniotic (DT) compared with trichorionic–triamniotic (TT) triplet gestations.Methods This is a retrospective cohort of all triplet gestations identified by first trimester ultrasound at an academic center between 2005 and 2016. Primary outcomes were the change in proportion of DT versus TT triplets over time and the number of fetuses at delivery. Secondary outcomes included differences in mode of conception and maternal/perinatal outcomes by chorionicity.Results Of 258 identified triplet pregnancies, 65.5% (n = 169) were TT. The proportion of DT versus TT triplets increased from 2005 to 2016 (p < 0.001). Women with DT triplets were more likely to deliver a singleton (41.4 vs. 11.2%, p < 0.001). Mode of conception was known for 248 women, of whom 93.5% (n = 232) conceived through infertility treatment. Types of infertility treatment differed by chorionicity (p < 0.001), with DT triplets more likely to conceive through in vitro fertilization (88.3 vs. 60.7%). Women with DT delivered earlier than TT triplets (31.0 ± 5.0 vs. 33.1 ± 3.5 weeks; p = 0.03).Conclusion The proportion of DT triplet gestations increased significantly over time. Women with DT triplets delivered on average 2 weeks earlier than TT triplets. Women with DT triplets were more likely to reduce to a singleton gestation.
Keywords: chorionicity; triplet gestation; triplet chorionicity; multifetal pregnancy reduction